2016
DOI: 10.1080/12265934.2016.1213139
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high-speed railroad on regional income inequalities in China and Korea

Abstract: The purpose of this study is to analyze the impact of opening high speed railroad (HSR) on the regional income inequalities in China and Korea. The convergence models are applied to test the effect of the HSR on regional growth in terms of GRDP per capita across 455 cities and counties along the Beijing-Shanghai HSR corridor and 112 cities and counties along the Seoul-Busan HSR corridor respectively. The results indicate that at national level, a trend of convergence emerges during the three-year period of ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…The risk of dying was 0.69 times (95% CI: 0.58-0.81) lower for females than for males. Recent studies noted higher cancer incidence and mortality among males compared to females [23][24][25]. According to our results, the risk of death in patients with cancer gradually increased with age.…”
Section: Discussionsupporting
confidence: 75%
“…The risk of dying was 0.69 times (95% CI: 0.58-0.81) lower for females than for males. Recent studies noted higher cancer incidence and mortality among males compared to females [23][24][25]. According to our results, the risk of death in patients with cancer gradually increased with age.…”
Section: Discussionsupporting
confidence: 75%
“…It is also true that HSR impact is larger in cities with HSR, even if it has an indirect impact on cities without HSR. Areas close to HSR stations may have faster economic growth than distant regions [21].…”
Section: Discussionmentioning
confidence: 99%
“…Jiang and Kim (2016) [21] proposed HSR impact on regional income inequality by using a convergence model in China and South Korea. The authors found that HSR networks reduced regional income disparity in both countries.…”
Section: High-speed Rail and Regional Developmentmentioning
confidence: 99%
“…Besides, some scholars pay attention to the social impact of HSR [17,18]. Chen et al, and Jiang, et al take explorative analysis on the impact of HSR on regional income disparities and found that HSR can accelerate regional economic convergence and reduce the regional income disparities [19,20].…”
Section: Literature Reviewmentioning
confidence: 99%